Density of crystalline lens and cornea in different trimesters of pregnancy. Issue 3 (June 2019) - Karakucuk, Yalçin; Altinkaynak, Hasan; Karakuçuk, Selim; Beyoglu, Abdullah; Çömez, Aysegul; Demir, Mustafa
Abstract: Purpose: To evaluate topographic measurements of the anterior segment and densitometric measurements of the cornea and lens by Pentacam HR in different trimesters of pregnancy. Methods: This prospective study included 150 healthy pregnant women in their first, second, or third trimester (Groups 1, 2 and 3, respectively) and 54 non-pregnant healthy women (Group 0). Topographic measurements, including central corneal thickness (CCT), corneal volume (CV), anterior chamber depth (ACD), corneal densitometry (CD) and lens densitometry (LD), were done with the Pentacam HR (Oculus, Wetzlar, Germany). The measurement results of the healthy pregnant women and non-pregnant healthy women were compared. Results: CD values were found in Group 1 to be 13.19, in Group 2 to be 13.16, in Group 3 to be 13.17 and in Group 0 to be 13.22 (p = 0.811). The mean Group 1, Group 2, Group 3 and Group 0 LD-horizontal was 5.40 ± 0.5, 5.47 ± 0.38, 5.53 ± 0.44, 5.36 ± 0.43, respectively. The mean Group 1, Group 2, Group 3 and Group 0 LD-vertical was 5.6 ± 0.43, 5.66 ± 0.32, 5.71 ± 0.40 and 5.5 ± 0.44, respectively. Area LD values were higher in the advanced trimester period, and the only statistically significant difference was between Group 3 and Group 0 (p = 0.025). The difference between three-dimensional (3D) and peak LD values was not statistically significant between the groups (p = 0.89 and p = 0.91, respectively). Discussion: The Pentacam HR seems to be an important option for the evaluation of LD, CD and topographic measurements of the anterior segment in pregnancy. In the present study, CD and LD, including LD-horizontal, LD-vertical, peak and 3D values, were not significantly different between pregnant women and non-pregnant women.